The Relationship Between Stress Levels and Carbohydrate Intake with The Nutritional Status of Students of SMPN 22 Surakarta - Layla Bonita Salsabila; Nur Lathifah Mardiyati; Firmansyah Firmansyah (Journal Research of Social Science, Economics, and Management, 2025)
Multifactorial elements, including psychological and dietary factors such as stress levels and carbohydrate intake, influence adolescent nutritional status. This study analyzed the relationship between stress and carbohydrate intake with the nutritional status of 9th-grade students at SMPN 22 Surakarta. Using a quantitative approach with a cross-sectional design, data were collected from 141 randomly selected students. Stress levels were measured using the DASS-21 questionnaire, carbohydrate intake was assessed through a 24-hour recall over three non-consecutive days, and nutritional status was evaluated via BMI-for-age (BMI/U) z-scores. Results indicated that students with poor nutritional status exhibited higher severe stress (28.6%) and lower carbohydrate intake (10.8%). Conversely, students with better nutritional status reported moderate stress (22.7%) and higher carbohydrate intake (25%). However, bivariate analysis revealed no statistically significant relationship between stress levels and nutritional status (p=0.714), nor between carbohydrate intake and nutritional status (p=0.676). These findings suggest that stress and carbohydrate intake alone are insufficient predictors of adolescent nutritional status. Further research should investigate other influencing factors such as physical activity, overall dietary patterns, sleep quality, and psychosocial environment to address adolescent nutritional health comprehensively.